Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Video Kontekstual Terhadap Penguasaan Konsep Fisika Peserta Didik - Selva Eka Yolanda; Gunawan Gunawan; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This study aims to examine the effect of the guided inquiry learning model assisted by contextual videos on the mastery of the physics concepts of students. This type of research is a quasi-experimental design with untreated control group design with pretest-posttest. The population in this study were all students of class X MIA SMAN 3 Mataram. Sampling uses a purposive sampling technique, so students selected class X MIA 3 as the control class and class X MIA 2 as the experimental class. The type of test used for concept mastery consists of 30 multiple choice questions. The average value of posttest mastery of concepts in the experimental class and control class is 73.20 and 66.18. The statistical analysis used for hypothesis testing in this study was the t-test with a significance level of 5%. Hypothesis test results show the value of t arithmetic 2.52 is greater than the value of t table that is 2.00 so that H0 is rejected and Ha is accepted it can be concluded that there is an effect of the guided inquiry learning model assisted by contextual videos on the mastery of the physics concepts of students.